Evaluating the Physical Development of Early Age Schoolchildren (7-10 Years): Cohort Study Results - M. V. Khodzhieva; V. A. Skvortsova; T. E. Borovik; L. S. Namazova-Baranova; T. V. Margieva; T. V. Bushueva; O. S. Melnichuk; S. V. Nekrasova (Union of pediatricians of Russia, 2016)
Background: Misbalance between energy intake and consumption is considered the main reason of obesity. However, over the recent years there has been a lot of emerging data concerning early origins of obesity that forms during intrauterine development and/or early age periods.Objective: Our aim was to study how physically developed are the children of early school ages.Methods: The study included children aged 7 to 10 years. Their physical development was assessed with the WHO AnthroPlus (2009) software.Results: 652 children were examined. Of them, balanced development was found in: according to the WAZ index (body mass/age) - 466/530 (87,9%) schoolchildren; HAZ index (height/age) - 620/652 (95,1%); BAZ (body mass index/age) - only 438/652 (67,2%) children. Excessive body weight was found in 61 (18,8%) of the 324 girls and 65 (19,8%) of the 328 boys (р = 0,891), obesity - in 24 (7,4%) and 52 (15,9%) children correspondingly (р = 0,038).Conclusion: Having evaluated the physical development of early aged schoolchildren between the ages of 7 and 10 years, it is possible to state that there is evidence in favour of higher readings of mass-weight indexes as compared to the standard WHO population. Every third early age schoolchild can have physical development deviations, at the same time boys are obese twice as often as girls.